A nők szerepe a Magyar Iparoktatás folyóiratban – a női iparoktatás és munkavállalás megítélésének változásai az első világháború éveiben - Vörös, Katalin (Per Aspera ad Astra, 2018)
Some historical and pedagogic works studied the history of the Hungarian vocational education in recent years. Only a few attention was given to the female industrial education, although the examination of these topic could give new aspects to the social process of 19–20th century, the changing gender roles and the emancipation efforts. The War definitely intensified the economic, social changes and the political process in the early 20th century. At the same time many questions has been arising in connection with the vocational education: How did the war affect the (female-)vocational education and the male-dominated public sphere? What kind of opinions and conceptions were prevailed about the women’s work and education? My study is seeking the answer to these questions. The representation of the female industrial education is examined in media history approach during the World War I in my paper, paying particular attention to one of the most important official journal the ‘Magyar Iparoktatás’ (Hungarian Industrial Education).